A Genus/Species Account of Scale‐Degree Qualia. (11th July 2022) - BRUSCHI, MICHAEL
ABSTRACT: Scale‐degree qualia are the fundamental building blocks of tonal cognition. Despite the recent flurry of scholarly activity surrounding their nature, certain conceptual entanglements persist. I argue that when scholars (and pedagogues) invoke the notion of scale degrees, they typically conflate two subcomponents of scale‐degree experience – which I call 'generic scalar position' and 'specific modal character' – and treat them as if they were one composite thing. In response, I propose an ordered‐triple notation for labelling scale degrees that insists on the representational separation of these two subcomponents, and I demonstrate through a series of analytical vignettes that conceiving of scale degrees in this manner can shed new light on a variety of common musical scenarios, from local tonicisations to large‐scale modulations to moments of tonal/modal ambiguity. This ordered‐triple notation is intentionally designed for a flexible domain of application, not just to European tonal music but also to Western popular music and more generally to any music in any of the seven diatonic modes.